Infusion of N‐acetyl cysteine during hypoglycaemia in humans does not preserve the counterregulatory response to subsequent hypoglycaemia. Issue 3 (15th May 2020) - Moheet, Amir; Kumar, Anjali; Zhang, Yuan; Eberly, Lynn; Coles, Lisa D.; Seaquist, Elizabeth R.
Abstract: Aim: Administration of N‐acetyl cysteine (NAC) during hypoglycaemia will preserve the counterregulatory response to subsequent hypoglycaemia in healthy humans. Methods: This was a randomized double‐blind cross over study where humans were given either a 60‐minute infusion of NAC (150 mg/kg) followed by a 4‐hour infusion of NAC (50 mg/kg) or saline starting 30 minutes before the initiation of a 2‐hour hypoglycaemic (HG) clamp at 8 am . After rest at euglycaemia for ~2 hours, subjects were exposed to a 2nd HG clamp at 2 pm and discharged home in euglycaemia. They returned the following day for a 3rd HG clamp at 8 am . Results: Twenty‐two subjects were enrolled. Eighteen subjects completed the entire protocol. The epinephrine response during clamp 3 (171 ± 247 pg/mL) following clamp 1 NAC infusion was lower than the response during the clamp 1 NAC infusion (538 ± 392 pg/mL) (clamp 3 to clamp 1 NAC: P  = .0013). The symptom response during clamp 3 (7 ± 5) following clamp 1 NAC infusion was lower than the response during the clamp 1 NAC infusion (16 ± 10) (clamp 3 to clamp 1 NAC: P  = .0003). Nine subjects experienced rash, pruritus or nausea during NAC infusion. Conclusion: We found no difference in the hormone and symptom response to experimental hypoglycaemia measured in subjects who were administered NAC as opposed to saline the day before. This observation suggests that further development of NAC as a therapy for impaired awareness of hypoglycaemia in patients with diabetes may be unwarranted. Abstract : Infusion of the antioxidant N‐acetyl cysteine during hypoglycaemia in healthy humans did not preserve the counterregulatory response to hypoglycaemia the next day. This observation suggests that further development of NAC as a therapy for impaired awareness of hypoglycaemia in patients with diabetes may be unwarranted.